Spaces of geographical thought deconstructing human geography's binaries - Cloke, Paul J.; Johnston, R. J. (Ronald John) (SAGE, 2005)
Examining key ideas - like space and place - which inform the geographic imagination, this text discusses the core conceptual vocabulary of human geography.